Sosialisasi dan Pendampingan Penggunaan Aplikasi Digital QRIS Sebagai Alat Pembayaran Sedekah pada Masyarakat Kelurahan Kratonan Kota Surakarta - Yuni Safitri; Eva Dewi Murdianingsih; Muhammad Yusuf Sofyan (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2022)
The community service activities carried out by IIM Surakarta as the integrative PKN and PKM program in 2022 used the socialization method regarding the benefits of using QRIS in the Kratonan sub-district, Surakarta city. Many still do not know the information and benefits of QRIS, so it is hoped that this community service will be able to help provide positive energy to the community. The community is transforming toward a cashless society. The results of this activity are immediately put into practice by the people in the Kratonan village to install and use the QRIS application in alms transactions. So the purpose of this community service is to educate the community in the Kratonan sub-district, Surakarta city, to be more advanced in managing alms through mosques so that transformation in the digital era can be achieved.